Assessing macroeconomic uncertainties for an emerging economy - Motilal Bicchal; S. Raja Sethu Durai (Asian Development Bank Institute (ADBI), 2020)
This study constructs the macroeconomic uncertainty indices for an emerging economy, India, and considers other macroeconomic uncertainty indices to evaluate their relative effectiveness in terms of tracing the business cycles and finding out the transmission channels consistent with theory. The study estimates a series of VAR models using quarterly data to identify different uncertainty channels of aggregate demand and supply. The derived measures of uncertainty are higher around recessions and other structural changes like demonetization and GST implementation in India. Further, the empirical results show that the effects of uncertainty shocks to different domestic variables are consistent with the supply side of the real-option channel, the demand side of the investment channel, and the precautionary channel. Finally, to understand the effects of international spillover, this study measured the impact of US uncertainty on domestic variables, and the results suggest that US uncertainty has much more impact than domestic uncertainty, suggesting a significant international spillover effect of uncertainty in the Indian economy. These findings provide a holistic examination of how uncertainty affects macroeconomic activity from an emerging economy perspective. The results also suggest that the news-based economic policy uncertainty index, which is widely used in developed countries has not properly captured the state of economic uncertainty in India.
Keywords: D80; E32; E66; P50; 330; business cycles; economic uncertainty; emerging market economy; spillover